Narasi Komodifikasi dan Relasi Kuasa pada Kumpulan Cerpen Nelayan Itu Berhenti Melaut Karya Safar Banggai - Saragih, Mike Wijaya; Prasetyo, Teguh; Sinulingga, Febrimarini; Ndoen, Gabriella (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2025)
Since the echo of the "back to sea" policy, there have been many things that have become the concern of the Indonesian government to gain revenue from Indonesia's marine resources, including its tourism potential. In implementing the program, several issues arose related to the welfare of the maritime community itself. In the collection of short stories "Nelayan itu Berhenti Melaut" by Safar Banggai, these issues are raised as the main narrative. Therefore, this article will try to dissect the issue of commodification narratives and power relations in several short stories in this collection of short stories. The analysis in this article will use a sociological approach, borrowing critical theories centered on the concepts of commodification and power relations. The results of this analysis indicate that the sea communities narrated in several short stories are bound by power relations that make their voices muffled and make them reified as objects. This form of commodification is not only seen in the objectification of society and its settlements, which are considered exotic, but also in socio-cultural practices that have changed because the traditions have been mortgaged